"Cell biology meets physiology: functional organization of vertebrate plasma membranes"--the immunological synapse. - Curado, S; Kumari, S; Dustin, M (2013)
The immunological synapse (IS) is an excellent example of cell-cell communication, where signals are exchanged between two cells, resulting in a well-structured line of defense during adaptive immune response. This process has been the focus of several studies that aimed at understanding its formation and subsequent events and has led to the realization that it relies on a well-orchestrated molecular program that only occurs when specific requirements are met. The development of more precise and controllable T cell activation systems has led to new insights including the role of mechanotransduction in the process of formation of the IS and T cell activation. Continuous advances in our understanding of the IS formation, particularly in the context of T cell activation and differentiation, as well the development of new T cell activation systems are being applied to the establishment and improvement of immune therapeutical approaches.